Do Public Relations and Journalism’s converging roles affect how they perceive each other? An Italian Outlook - Valentini, Chiara (Instituto de Investigación en Relaciones Públicas, 2014)
Media relations is historically a core activity qualifying public relations from other communication-related professions and is widely practiced in many organizations. Despite the increasing use of digital media to directly communicate with publics, journalists are still key stakeholders for organizations. Also communications by organizations have become more and more mediatized and at the same time more and more journalists are switching to a public relations career. Yet, if more journalists are becoming public relations practitioners and more public relations practitioners are adopting journalistic working practices, does this change the way these communicators perceive themselves and the other profession? The aim of this study is to provide some insights from a southern, Latin country, Italy, on how Italian public relations practitioners and journalists perceive their and the other profession, roles, practices and relationships. A mixed method, including face-to-face interviews and an online survey, was used to collect and analyse the data. Results indicate that public relations and journalism’s converging roles is affecting how these communicators perceive each other in a favorable manner. Furthermore, the impact is more evident in public relations practitioners since their opinions of journalism and journalists correspond to journalists’ selfevaluations.
¿Cómo perciben los Relaciones Públicas y los Periodistas sus profesiones? Una mirada desde Italia
Keywords: Relaciones públicas; Periodismo; Public Relations; Journalism; Perceptions